Job growth, accessibility, and changing commuting burden of employment centres in Melbourne. (October 2020) - Li, Tiebei; Dodson, Jago
Abstract: How transport and employment agglomeration enhance urban productivity is a fundamental problem for many cities. Internationally, there has been a great deal of interest in the effect of employment concentration on urban productivity, but very few studies have examined its effect on worker commuting burdens and transport costs. This paper aims to advance international knowledge by measuring job growth and costs of labour market access between 2011 and 2016 for employment centres (EC) in Melbourne, Australia. A comprehensive transport cost model is used that incorporates detailed transport costs and travel times associated with transport modes. By tracking job growth and changes in worker commuting burdens, this paper distinguishes 'high-cost' ECs from 'low-cost' ECs, for their respective labour pools, and identifies which ECs offer opportunities for better transport outcomes. The results show that well-planned public transport (PT) systems and residential development, coupled with walking and cycle networks, are important features of ECs experiencing lower commuting burdens. Drawing upon the conclusions, this research recommends more effective approaches by governments to foster effective investments in urban infrastructure and discusses how broader policy and investment decisions can align to optimise employment agglomeration and minimise negative transport impacts.